What Drives Satisfaction and Continuance Intention to Use E-Learning? : A Case of Dance Academy Students in Chengdu, China - Li, Mengke (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
This study aims to explore the factors that significantly impact the e-learning satisfaction and continuance intention of dance academy students in Chengdu, China. The Technology Acceptance Model (TAM), Expectation Confirmation Model (ECM), and Information Systems Success Model (ISSM) serve as the foundation for the conceptual framework in this study. The study explores the key constructs from previous studies to propose a conceptual framework, including service quality, perceived ease of use, perceived usefulness, confirmation, information quality, satisfaction, and continuance intention. The quantitative questionnaire was distributed to 476 undergraduate students in Dance Academy at Sichuan University. The sampling methods include judgmental, quota and convenience sampling. Additionally, this study used confirmatory factor analysis and structural equation modeling as statistical analysis methods. The analysis showed that all six hypotheses were supported. Students will be more likely to use e-learning in the future if they are very satisfied with their online learning experience. The usefulness of e-learning is also significantly impacted by perceived ease of use, information quality and service quality.